The Effect Of Nursing Intervention On The Quality Of Life Of Hypertension Patients With Complications - Imam Safii (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Hypertension with complications is a chronic health problem that significantly impacts patients' quality of life. Complications of hypertension, such as heart disease, stroke, and kidney disease, not only affect the patient's physical condition but also impact their psychological, social, and environmental aspects. The reduced quality of life in patients with hypertension with complications is often caused by activity limitations, dependence on long-term medication, and anxiety about their health condition. Therefore, comprehensive efforts are needed to improve patients' quality of life through structured and continuous nursing interventions. This study aims to determine the effect of nursing interventions on the quality of life of hypertensive patients with complications. The study used a quasi- experimental design with a pretest - posttest approach. without control group. The study sample consisted of 50 hypertensive patients with complications selected using a purposive sampling technique. Nursing interventions were provided for four weeks, including health education, lifestyle management, psychosocial support, and monitoring of medication adherence. Patients' quality of life was measured using the WHOQOL-BREF instrument, which covers physical, psychological, social relationships, and environmental domains. Data were analyzed using a paired t- test with a significance level of α = 0.05. The results showed a significant improvement in the quality of life of patients after nursing intervention, with a p -value <0.05. Improvements in quality of life were seen across all domains, particularly in the physical and psychological aspects. It was concluded that nursing interventions had a positive effect on improving the quality of life of patients with hypertension with complications. Therefore, comprehensive nursing interventions need to be implemented continuously in nursing care for patients with hypertension with complications.